On the use of venturi tubes in aeration - Baylar, Ahmet; Ozkan, Fahri; Unsal, Mehmet (Wiley-V C H Verlag Gmbh, 2007)
The ecological quality of water depends largely on the amount of oxygen that the water can hold. The higher the level of dissolved oxygen, the better the quality of a water system. By measuring dissolved oxygen, scientists determine the quality of water and health of an ecosystern. Oxygen enters water by entrainment of air bubbles. Many industrial and environmental processes involve the aeration of a liquid by such entrainment of air bubbles. Venturi aeration is a method of aeration that has become popular in recent years. When a minimal amount of differential pressure exists between the inlet and outlet sides of a venturi tube, a vacuum (air suction) occurs at the suction holes of the venturi tube. The present paper describes the effect of Reynolds Number, air inlet hole diameter, inlet diameter, pipe length, and angle of pipe downstream of the venturi tube, on the air injection rate. It is observed from the results that venturi tubes have high air injection efficiencies. Therefore, venturi tubes can be used as highly effective aerators in ponds, lakes, fish hatcheries, water treatment plants, etc.
Keywords: aeration; air injection; venturi; water quality